Evaluation of strong ground motion for Yogyakarta depression area, Indonesia - Myo Thant; Subagyo Pramumijoyo; Heru Hendrayana; Hiroshi Kawase; Agus Darmawan Adi (Geological Engineering Department Universitas Gadjah Mada, 2015)
The probabilistic seismic hazard maps are developed for Yogyakarta depression area. The earthquake catalog of ANSS (1970-2007) is taken into account with the complement of NEIC (USGS, 1973-2007) and the records of BMG (2000-2004). On the basis of seismicity of the area, tectonics and geological information, the seismic source zones are characterized for this area. The seismicity parameters of each seismic source are determined by applying the classical Gutenberg-Richter recurrence model, regarding the historical records. The attenuation relation for Yogyakarta depression area cannot be evaluated since the sufficient strong ground motion records are not available for this region. Therefore the attenuation relations which were developed for other territories as Europe and Japan are used for the present hazard calculation by validating, using the aftershocks records, modeling the peak ground acceleration maps for the recent event, 27 May, 2006, Yogyakarta earthquake inserting the damage area distribution pattern. The probabilistic seismic hazard maps are finally developed by using the McGuire (1976) EQRISK computer program by modifying for the present purpose. The seismic hazard maps expressed in term of peak ground acceleration are developed for the recurrence intervals of 10, 50, 100, 200 and 500 years